Statek jako peculium w rzymskim prawie klasycznym - Zaborowska, Anna (Studia Iuridica Toruniensia, 2011)
<!–[if gte mso 9]> <![endif]–> Classical Roman Law sources contain information about the ship managed by the servus peculiaris. Although there are many jurists’ opinions about conducting seaborne business by the servus peculiaris, there are none regarding the obtaining of the ship. How the ship was transferred to the slave? Was the maritime business the whole peculium or just a part of it? Servus peculiaris was acting as the exercitor navis, this means that rules regarding the appointment of the captain (preapositio) cannot be applied. What rules should apply to the ship if it was administered as the peculium? The aim of this paper is to provide the answers to those questions. <!–[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>